Democracy and Citizenship - Fernández García, Eusebio (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
The paper focuses upon the indubitable interrelation between the concept of citizenship and democratic institutions.  Citizenship is the strongest nexus that there is between the inhabitant of a state and the state itself.  A democracy is a true democracy only if citizens have an effective and adequate participation in the political process, and the individual is a true citizen only if the regime is a democratic one that guarantees the rights of the individual.  The analysis of the historic democracy of Athens serves to establish the deficiencies and the limitations of any democracy that excludes.  Democracy, in its true sense, requires a cosmopolitan approach with cosmopolitan rights for its citizens who should coexist within the limits of national boundaries: such is one of the challenges of politics and law today.
Keywords: citizenship; democracy; pluralism; constitutional patriotism; cosmopolitan patriotism; territorial frontiers